Mindfulness-based stress reduction for chronic pain and health-related quality of life after intensive care unit discharge - Damico, Vincenzo; Cossalter, Luca; Murano, Liana; Latina, Roberto (Acta Biomedica Atenei Parmensis, 2025)
Aim: To test the efficacy of a mindfulness-based stress reduction (MBSR) program on pain management and on quality of life among chronic pain patients discharged from the intensive care unit (ICU). Methods: A mindfulness-based stress reduction intervention, aimed at improving pain management was implemented in a sample of 43 survivors of critical illness who suffered from chronic pain at an ICU. In this observational study, data were collected before (T0= 12 months after ICU discharge) and after the adoption of a MBSR program (T1= 10 months after intervention). The Brief Pain Inventory-Short Form (BPI-SF) and EuroQol-5 Dimension (EQ-5D) were used. Results: The Brief Pain Inventory showed a significant reduction in worst pain in the last 24 h (p< .001), least pain in the last 24 h (p= .011), pain on average (p< .001), and in terms of pain interference with mood (p= .002) and with sleep (p< .001). EQ-5D showed a significant reduction in the perception of moderate or extreme pain/discomfort (p= .009) and moderate to severe problems with anxiety/depression (p= .031). Conclusion: MBSR program seems to improve chronic pain intensity and to reduce the negative interference of pain on quality of life. Although the results are statistically significant, they do not appear to be clinically relevant. However, further studies with larger sample sizes and control groups are needed.